Exogenous factors of memory formation about the great soviet era in contemporary Russia - Larionov, Aleksey; Baghdasaryan, Vardan; Fedorchenko, Sergey; Shults, Eduard (Linguistics and Culture Review, 2021)
This article is devoted to the analysis of exogenous factors in the formation of the historical memory of Russian society about the Soviet era. The author refers to those components of the Russian information and cultural space that are created and broadcast into the consciousness of Russian society with direct influence and interest of foreign entities external to Russia. On the basis of facts and texts, conclusions are made about the systematic and consistent nature of attempts to influence the historical memory of Russian society in order to radically transform Russian national-historical consciousness and a sense of historical identity. The diversity of such effects is also noted. Despite the long and cumulative nature of attempts at external influence on the Russian memorial culture and social memory, a high degree of stability of the collective memory of Russian society should be stated. Not least, this is achieved thanks to the thoughtful historical policy of the Russian state over the past 15-20 years.